The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00333549211021146
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Intensive Care Admissions in a Pregnant and Postpartum Population, Hawai‘i, 2012-2017

Abstract: Objective Maternal morbidity and mortality is a global concern despite advances in medical care and technology and improved economic resources of nations worldwide. The primary objective of our study was to describe racial/ethnic disparities in severe maternal morbidity by using admission to an intensive care unit (ICU) as a marker. The secondary objective was to evaluate associations between patient characteristics, including obstetric outcomes, and severe maternal morbidity. Methods This retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Few studies examined social determinants of health among women with SAMM in the ICU, with just age routinely reported in all studies. Most did not report on socio-economic status, and in those studies that did, there was a higher proportion of women who were poorly educated, from rural areas, and with low incomes, and in high income countries, either Black/Afro-American [7,37] or others of an immigrant/minority ethnicity background [40,46]. These indicate that it is important to gain more insight into immigration background, and investigate the relevance of length of migrant status, country of birth or origin, language, and other characteristics that may contribute to access and engagement with a health care service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies examined social determinants of health among women with SAMM in the ICU, with just age routinely reported in all studies. Most did not report on socio-economic status, and in those studies that did, there was a higher proportion of women who were poorly educated, from rural areas, and with low incomes, and in high income countries, either Black/Afro-American [7,37] or others of an immigrant/minority ethnicity background [40,46]. These indicate that it is important to gain more insight into immigration background, and investigate the relevance of length of migrant status, country of birth or origin, language, and other characteristics that may contribute to access and engagement with a health care service.…”
Section: Discussionmentioning
confidence: 99%
“…Data on smoking among maternal ICU admissions were described in fourteen studies from high-income countries (Australia, Canada, Finland, Hong-Kong, Israel, New Zealand, UK and USA including Hawaii) and one upper-middle-income country (Peru), with rates from 4.0% in Hong Kong [67] to 42.0% [68] in Australia. Madan et al (2009) [41] reported that smoking was signi cantly associated with obstetric ICU admissions; but similar results were not found in the USA (37,40), UK [39] and Canada [69].…”
Section: Smokingmentioning
confidence: 94%
See 2 more Smart Citations
“…Analysis of SMM incidence timing-differences amongst racial and ethnic groups between 2010 and 2014 found that during delivery hospitalization there was a gap in SMM between non-Hispanic-White women and all others, but during the six weeks after delivery hospitalization discharge, only the Black-White gap remained [9 ▪ ]. Studies examining individual SMM indicators show that peripartum hysterectomy, perioperative blood transfusions, and intensive care unit (ICU) admissions have increased rates for Black and Hispanic women (and other non-White women) [10–12]. NIS analysis of data between 2007 and 2017 showed that Black women, compared to White women, had the highest adjusted odds of major cardiovascular events (mortality, myocardial infarction, stroke, pulmonary embolism, peripartum cardiomyopathy) among pregnant and postpartum women [13 ▪ ].…”
Section: Epidemiology Of Obstetrical Disparitiesmentioning
confidence: 99%